2021
DOI: 10.22437/jisic.v12i2.11243
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Laboratorium Virtual Kimia Teknik untuk Meningkatkan Keterampilan Berpikir Kritis dan Proses Sains Mahasiswa

Abstract: [Development of The Virtual Laboratory of Engineering Chemistry to Increase Students' Critical Thinking and Science Processes Skills] TTujuan penelitian ini yaitu untuk mengembangkan media pembelajaran laboratorium virtual kimia yang didesain untuk dapat meningkatkan keterampilan berpikir kritis dan keterampilan proses sains mahasiswa secara mandiri dimasa pandemi covid-19. Pendekatan yang digunakan yaitu penelitian dan pengembangan dengan model ADDIE. Validasi ahli materi dan media digunakan untuk menilai kel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…Based on the validation results of both material experts and media, it can be concluded that the android-based chemistry virtual laboratory media on acid-base materials made by researchers obtained an assessment with very valid criteria, so it means that it is valid to be used as a chemistry learning medium. This is in line with the research conducted by Edi Elisa that developing a virtual chemistry laboratory media also obtained a very feasible assessment after the validity test stage was carried out (Elisa et al, 2020).…”
Section: Develop Stagesupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the validation results of both material experts and media, it can be concluded that the android-based chemistry virtual laboratory media on acid-base materials made by researchers obtained an assessment with very valid criteria, so it means that it is valid to be used as a chemistry learning medium. This is in line with the research conducted by Edi Elisa that developing a virtual chemistry laboratory media also obtained a very feasible assessment after the validity test stage was carried out (Elisa et al, 2020).…”
Section: Develop Stagesupporting
confidence: 83%
“…The results showed that the average percentage values were 94% and 90.5% obtained from the material and media expert validators with very valid criteria. Meanwhile, based on the results of trials with small group samples and large groups, they obtained an average percentage value of 97.07% and 96.8% with very practical criteria for use (Elisa et al, 2020). The virtual laboratory media that can be used during the learning process can vary, one of which is an Androidbased virtual laboratory media.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this assessment, it indicates that the Virtual Laboratory developed is feasible to be implemented in learning, especially in Plant Tissue Culture practicum activities. The same thing was explained by Elisa (2020) who stated that the results of the Virtual Laboratory assessment were in the very good category indicating that the media was very feasible to be tested in learning to meet the needs of learning media in schools. The same thing was also expressed by Kurniawan (2021) that a Virtual Laboratory with a very valid level can be used and practiced on students to have positive implications for student learning activities.…”
Section: Resultsmentioning
confidence: 64%
“…Kemampuan berpikir kritis ialah salah satu keterampilan yang perlu dimiliki siswa di abad 21 saat ini. Berpikir kritis adalah kegiatan menyimpulkan dengan menganalisis suatu keadaan berdasarkan fakta dan bukti (Agnafia, 2019;Elisa et al, 2021). Setiap pembelajaran harus melatih kemampuan berpikir kritis siswa, hal ini juga berlaku pada pembelajaran kimia.…”
Section: Pendahuluanunclassified